AN ANALYSIS OF ENGLISH ABSTRACT WRITTEN BY THE PARTICIPANTS ON NATIONAL SEMINAR PROCEEDING - Siti Nuraminah; Pipit Rahayu (JEE (Journal of English Education), 2019)
This research investigated about the English Abstract Written By The Participants on national proceeding conducted by University of Pasir Pengaraian. The purpose of this research was to analyzed English Abstract Written By The Participants. This research was descriptive qualitative design. The population of this research was 45 abstract. The sample of this research was 45 abstract. The data was to analyzed by three raters. Based on the two indicator that have given by the researcher. The result of this research that showed based on the first indicator was categorized in good level, mean while The result of this research based on the second indicator was categorized in fair level. The weaknesses of the participants in writing abstract, most of them did not write the conclusion in their abstract. Theweaknesses of the participants in writing abstract, most of them did not written the conclusion, suggestion, and not using ARIAL 11 in their abstract=